A Web of Coagulotoxicity: Failure of Antivenom to Neutralize the Destructive (Non-Clotting) Fibrinogenolytic Activity of Loxosceles and Sicarius Spider Venoms - Dwin Grashof (Toxins, 2020)
Envenomations are complex medical emergencies that can have a range of symptoms and sequelae. The only specific, scientifically-validated treatment for envenomation is antivenom administration, which is designed to alleviate venom effects. A paucity of efficacy testing exists for numerous antivenoms worldwide, and understanding venom effects and venom potency can help identify antivenom improvement options. Some spider venoms can produce debilitating injuries or even death, yet have been largely neglected in venom and antivenom studies because of the low venom yields. Coagulation disturbances have been particularly under studied due to difficulties in working with blood and the coagulation cascade. These circumstances have resulted in suboptimal spider bite treatment for medically significant spider genera such as Loxosceles and Sicarius. This study identifies and quantifies the anticoagulant effects produced by venoms of three Loxoscles species (L. reclusa, L. boneti, and L. laeta) and that of Sicarius terrosus. We showed that the venoms of all studied species are able to cleave the fibrinogen Aα-chain with varying degrees of potency, with L. reclusa and S. terrosus venom cleaving the Aα-chain most rapidly. Thromboelastography analysis revealed that only L. reclusa venom is able to reduce clot strength, thereby presumably causing anticoagulant effects in the patient. Using the same thromboelastography assays, antivenom efficacy tests revealed that the commonly used Loxoscles-specific SMase D recombinant based antivenom failed to neutralize the anticoagulant effects produced by Loxosceles venom. This study demonstrates the fibrinogenolytic activity of Loxosceles and Sicarius venom and the neutralization failure of Loxosceles antivenom, thus providing impetus for antivenom improvement.